Efficiency in Cow-Calf Systems With Different Ages of Cow Culling - Sessim, Amir Gil; de Oliveira, Tamara Esteves; López-González, Fredy Andrey; de Freitas, David Santos; Barcellos, Júlio Otávio Jardim (Frontiers in Veterinary Science, 2020)
The bioeconomic efficiency of cow-calf systems was compared by a deterministic dynamic simulation. The simulation model considered stable cow-calf systems differentiated by the maximum age for culling cows, lifetime, culled at four years old; five years old ; six years old; seven years old; eight years old ; nine years old ; ten years old; eleven years old ; twelve years old and thirteen years old. The necessary supply of metabolizable energy for the herd was established as natural grasslands, cultivated pasture in the winter/spring, and pre-dried pasture produced by the system. The biological efficiency of the systems was considered the ratio between the production of total live weight and the metabolizable energy consumed over one production cycle. Economic efficiency was determined by the ratio between gross margin and production area and the ratio between gross margin and number of cows . Bioeconomic efficiency was determined by a simple linear regression between biological efficiency , economic efficiency per area, and economic efficiency per cow. The efficiency of the animal unit, considering biological efficiency and economic efficiency per area were better in the system that culled cows at four years old, while economic efficiency per cow was better in the system that culled cows at thirteen years old. In determining the bioeconomic efficiency of the systems, the best results were found in the system that culled cows at six years old, which suggests that the best efficiency of a cow-calf herd is reached when the adult age and mature weight of the cow are reached, and there is no more energy used for growing. The results indicate that stable cow-calf herds express their best biological efficiency and economic efficiency per area when the cow culling age is lower. However, economic efficiency per cow depends on cows that remain in the herd as long as possible. The culling age of cow that balances these biological and economic indicators is reached around five and half years.